A double blinded randomized placebo trial of Bifidobacterium animalis subsp. lactis BLa80 on sleep quality and gut microbiota in healthy adults - Yinhua Liu; Yanyan Chen; Qingya Zhang; Yanyan Zhang; Fei Xu (Scientific Reports)
Abstract Human sleep quality is intricately linked to gut health. Emerging research indicates that Bifidobacterium animalis subsp. lactis BLa80 has the potential to ameliorate gut microbiota dysbiosis. This randomized, placebo-controlled study evaluated the impact of BLa80 supplementation on sleep quality and gut microbiota in healthy individuals. One hundred and six participants were randomly assigned to receive either a placebo (maltodextrin) or BLa80 (maltodextrin + BLa80 at 10 billion CFU/day) for 8 weeks. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI), a validated tool consisting of 18 items assessing seven components of sleep quality over a one-month period, and the Insomnia Severity Index (ISI), a secondary measure of insomnia severity. Gut microbiota changes were assessed using 16S rRNA sequencing, while the in vitro gamma-aminobutyric acid (GABA) production capacity of BLa80 was analyzed by HPLC. After 8 weeks, the intervention group exhibited a significant reduction in the PSQI total score compared to the placebo group, suggesting improved sleep quality. While no significant changes in alpha diversity were noted, beta diversity differed markedly between groups. The gut microbiota predominantly consisted of Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria and Fusobacteria, collectively accounting for over 99.9% of the gut microbiota. Statistical analysis showed that BLa80 significantly decreased the relative abundance of Proteobacteria phylum and increased the abundance of Bacteroidetes, Fusicatenbacter, and Parabacteroides compared to placebo. PICRUSt2 analysis indicated noteworthy enhancements in the pathways of purine metabolism, glycolysis/gluconeogenesis, and arginine biosynthesis due to BLa80 intervention. Moreover, BLa80 demonstrated notable GABA production, potentially contributing to its effects on sleep quality modulation. These results demonstrate the ability of BLa80 to improve sleep quality through modulating gut microbiota and GABA synthesis, highlighting its potential as a beneficial probiotic strain.